Recognizing and Rewarding Engagement with Open Educational Resources: Towards Sustainable Institutional Change (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The integration of open educational resources (OER) into mainstream higher education practice has long been recognized as a catalyst for innovation, equity, and sustainability. Yet, despite growing availability of high-quality open content, widespread adoption by educators remains limited. One of the critical barriers to sustainable engagement with OER is the lack of formal but also informal recognition for the time, expertise, and pedagogical care invested in creating, adapting, and sharing these resources. While institutional strategies increasingly refer to the value of openness, concrete models for recognizing and rewarding such efforts are still underdeveloped.  At HAN University of Applied Sciences in the Netherlands, we are addressing this challenge through the "HAN Approach Digital Educational Resources" project. This institutional initiative promotes open sharing and reuse of digital educational resources, with a particular focus on supporting educators in adopting OER in meaningful and lasting ways.  Central to this effort is a recognition and reward model that seeks to integrate open practices into the core structures of academic work. In this presentation, we introduced the development, and implementation of this model, which draws from both empirical findings, and theoretical insights into motivation, professional identity, and institutional change. The model recognizes that motivation to engage with OER is shaped by a complex interplay of intrinsic factors---such as the desire to improve education or collaborate openly---and extrinsic conditions, including workload models, promotion criteria, and visibility of contributions. By connecting these dimensions, the model supports both individual agency and systemic transformation.  Rather than treating OER as an isolated or extra-curricular activity, the model positions open practices as integral to teaching excellence and educational innovation. It identifies opportunities for making open contributions visible and valued across multiple levels: in individual professional development, within communities of practice at the team or faculty level, and in institutional policies related to quality assurance and human resources (HR). At HAN, we are currently embedding this model into our professional development offerings, piloting the use of extrinsic reward options (such as open badges and awards) but also more intrinsic and informal ways to recognize and reward our educators (such as social recognition, knowledge sharing, and autonomy). We are also working with the HR department to align recognition of OER work with broader evaluation and reward processes.  This presentation reflected on key challenges and lessons learned from our implementation process, including tensions between formal and informal recognition, issues of equity in access to recognition, and the need for institutional alignment. We  also positioned our approach within national and international developments, including the Dutch program for digitalization in education (Npuls), the Dutch Recognition and Reward program for academics and European conversations around open recognition.  Our aim was to provide participants with both a conceptual framework and practical insights into how institutions can create a culture in which open educational practices are not only encouraged but structurally supported. We believe that recognizing and rewarding engagement with OER is not merely a matter of policy, but a necessary step in transforming educational ecosystems towards openness, collaboration, and shared  responsibility. Keywords: open educational resources, recognition and reward